Money supply, interest rate, liquidity and share prices: A test of their linkage - Mohamed Ariff; Chung, Tin-Fah *; Shamsher M. (Elsevier Ltd, 2012)
This paper reports new evidence of a liquidity effect on share prices from money supply changes. Money supply impacts on interest rate and liquidity were first proposed in 1969 and there is evidence that money supply increase leads to interest rate decline. Yet the proposition that money supply increase should lead to liquidity surge – thus to credit expansion – has yet received unanimous empirical support. Using quarterly data over 1968-2011, our results from a two-stage simultaneous solution of a system of equations indicate that money supply changes lead to a positive liquidity effect, as per the theory prediction. By extending the liquidity equation to asset prices, we also show that liquidity change has a significant positive effect on share prices, after controlling the effect of earnings. These findings, obtained after solutions to serious econometric issues of existing studies, appear to provide a clear verification of theory on the money supply effect on liquidity and on asset price.